A study of factors influencing eye screening: Descriptive findings - Mat Isa, Rif'atunnailah; Saidi, Sanisah; Salam, Adzura; Jamaludin, Sumaiyah @ ThandarSoe (2017)
Introduction: Individuals with Diabetes Mellitus (DM) are at increased risk for developing diabetic ocular complications. This study was carried out to determine factors influencing eye screening among Diabetes Mellitus patients. The descriptive findings of participants’ sociodemographic data will be discussed. Materials and Method: A cross-sectional survey was conducted at the few selective Primary Health Centers and endocrine clinics, Hospital Tengku Ampuan Afzan (HTAA) in Kuantan, Pahang. A total number of 170 diabetic patients were recruited for the purpose of this study. Questionnaire for this survey was adapted and modified from Knowledge, Attitude and Practice (KAP 2008) with the overall Cronbach Alpha score was 0.5. Descriptive statistics was referred to evaluate the data. Results: Participants’ mean age was 55.5 years old (SD ± 11.22), with age range between 20 years and 79 years old. From 170 participants, 51 male (30%) and 119 female (70%) were involved in this study. Majority of 139 participants (81.8%) were Malay. For educational level, 74 participants (43.5%) have the secondary education, only 12 participants (7.1%) have tertiary education and the rest of 43 participants (25.3%) have no formal education. The majority of participants (71.2%) have the monthly income less than RM 1000 and only 7 (4.1%) have monthly income of RM 4000 and above. Almost all patients (168 participants or 98.8%) have type 2 Diabetes Mellitus (DM). The majority of 65 patients (38.2%) were first diagnosed to have diabetes between 1 to 5 years duration, and only 10 patients (5.9%) diagnosed to have diabetes of 15 years and above. Most of the participants (109 or 64.1%) have a family history of DM. As for current treatment, the majority of them are taking oral medication 136 (80.0%). Conclusion: The main background characteristics of DM patients in current study were female, Malay, low household income and family trait with DM.